RANCANG BANGUN APLIKASI BROKER INSURANCE SYSTEM MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT PADA PT. CIPTA INTEGRA DUTA - Arfin Mustofa; Rahmawati (CV. Multi Kreasi Media, 2024)
PT Cipta Integra Duta, known as Integra is engaged in the insurance brokerage business. In the operational implementation of the integrated company, an IBOSS application is available but it still uses the old technology, namely codeigniter version 3 combined with Senchajs version 3. This causes the company to have many obstacles in following the digitalization era. In this application there is no activity log for each department, and in inputting memberships, it still uses forms that are entered one by one so that it becomes less efficient if there is a large amount of data. For the storage of company files, they still use printed documents. Based on these problems, a research was conducted to create an broker insurance system application. The research methodology used is the method of interview, observation, and literature study, while the system development methodology uses the Rapid Application Development (RAD) method and the Unified Modeling Language (UML) as a system description. For the manufacture of the system using the php programming language with the laravel framework as an Open API, reactjs as data visualization and Amazon S3 as data storage. The results of this study are that this application can make it easier to track activities from client data, find the files needed through the application, the process of entering client membership data is only enough by using an excel file and processing data stored centrally and integrated into the database.